Pengetahuan Pajak Mempengaruhi E-Faktur, Informasi Pajak, dan Kewajiban Pajak - Avita Anggraeni; Wulan Nur Maulida; Irda Agustin Kustiwi (Pusat Riset dan Inovasi Nasional, 2024)
Taxes are money we should give to governments, and use them to make important decisions and plans. Better technology has made paying taxes easier by using computers instead of paper. Taxpayer awareness is when people understand and agree to pay taxes honestly. Some researchers are trying to determine whether using computers to pay taxes and providing information about taxes will help people understand and pay taxes better. They asked people in the survey for more information. To see the data they collected, they used a special computer program called SPSS. The individuals they study are those who have to pay taxes. Those they study must pay taxes. Studies show that using computers and providing information about taxes can help people pay taxes, but just because people know about taxes doesn't mean they will pay them right away.